Bambuina bambui: A new genus and species of cave cricket from brazil (orthoptera: Grylloidea: Phalangopsidae: Luzarinae) - De A. G. de Mello, Francisco [UNESP]; Horta, Lília S.; Bolfarini, Marcio P. [UNESP] (My University, 2013)
Bambuina bambui, a new genus and species of phalangopsid cricket, is described from Gruta do Centenário, a quartzite cave located in Serra do Inficionado (Inficionado Ridge), a subset of mountains belonging to the Serra do Caraça (Caraça Ridge) complex in the State of Minas Gerais, Brazil. Copyright © 2013 Magnolia Press.
Keywords: Cave cricket; Description; Grylloidea; Luzarinae; Phalangopsidae